TI_GERICHTE 11.2010.6 vom 27. Januar 2010 , Nomina di un amministratore della successione "se non sono conosciuti tutti gli eredi" - TI Tribunale d'appello (2010)
Nomina di un amministratore della successione "se non sono conosciuti tutti gli eredi"